Delay Mechanism of β→δ Phase Transition of Cyclotetramethylene Tetranitramine in Polymer Bonded Explosive Formulations by Heat Conduction Obstacle. Issue 4 (23rd February 2016) - Dai, Xiaogan; Xu, Jinjiang; Wen, Yushi; Li, Yubin; Huang, Fenglei; Li, Ming; Zeng, Qun
Abstract: The β→δ phase transition (PT) of cyclotetramethylene tetranitramine (HMX) plays an important role in the safety of explosives when they are exposed to heat. In this work the effect of HMX content on the PT of HMX in Polymer Bonded Explosive (PBX) is reported. Using in situ X‐ray diffraction (XRD) test combined with quantitative analysis, the dependence of the PT temperature and dynamic behavior of HMX in PBX formulations [HMX+triaminotrinitrobenzene (TATB)+Olefin] on the content of HMX is investigated. The results show that the β→δ PT temperature gradually increases with the reduction of HMX content and with the increase of TATB content. Additives of TATB and olefin in high concentration can form compact coatings on the HMX crystals. Such coatings can delay the nucleations of δ‐HMX by inhibiting the volumetric expansion during PT. Moreever, these coatings separate the HMX crystals and build up a heat conduction obstacle. As a result the growths of δ‐HMX are also suppressed by the coatings. In contrast, fewer additives lead to larger free surface area of HMX, which accelerates the PT. Abstract :